Implementasi Model Flowchart Perancangan Sistem Informasi Akuntansi untuk Permintaan Dana/Advance - Samuel Ratumurun; Chricela Natalia Joseph (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2023)
Profiting and staying away from the practices of administrative and financial manipulation is everyone's goal in trying. It is,largely determined by a decision-making process that is based on accurate, relevant, and timely information. This goal can only bemet if marketing, production, and labor relations information, as well as financial data information, are properly designed andimplemented in the production of an accountable document-based accounting information system. In this study, we focused on the implementation of the flowchart model in the design of the information system for accounting for requests for funds/advances as one of the company's expenditure cycles, which is focused on designing and structuring the flow of documents requesting funds or advances needed by the accounting and finance departments to finance project needs and routine company needs with mechanistic pay in advance, using observational methods, interviews and literature studies. The implementation of this model is expected to improve the efficiency and effectiveness of the company's business processes in managing the demand for funds and advances. Even though in the design process, several obstacles to the implementation of the flowchart model were found, such as limited human resources and available technology, this condition can be overcome by conducting training for employees and developing better technology. With the hope that the results of this research can contribute to the development of an accounting information system for companies.